PENGARUH TINGKAT UTANG, INTENSITAS ASET TETAP, INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Wardhani, Ritma Putri; Supriadi, Adi (Jurnal Nusa Akuntansi, 2025)
This research aims to examine the effect of debt level, fixed asset intensity, inventory intensity on tax management with firm size as a moderating variable. This research takes a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is Panel Data Regression Analysis using Eviews version 12 application. The population used in this research is non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The data collection technique in this research is a purposive sampling technique with a population of 129 companies becoming the final 22 company samples or 110 observation data processed in this research. The research results showed that debt level, fixed asset intensity and inventory intensity affect tax management simultaneously. Fixed asset intensity partially affects tax management and debt level, inventory intensity has no effect on tax management. Firm size cannot moderate the effect of debt level, fixed asset intensity and inventory intensity on tax management.